Excursion business in the context of sustainable tourism development - Hutsal, Liudmyla (Journal of Education, Health and Sport, 2023)
The article examines the role of excursion activities in the development of sustainable tourism as an important area of the modern tourism industry. Sustainable tourism, which is guided by the principles of environmental responsibility, social inclusion and economic sustainability, is aimed at preserving natural and cultural resources and ensuring the long-term development of local communities. Excursion business, as one of the main components of tourism services, has a significant potential for implementing sustainable tourism ideas due to the possibility of direct influence on the minds of tourists, promotion of cultural heritage and support for the local economy. In addition, sightseeing is a powerful tool for introducing tourists to the cultural heritage of the region. Excursions focusing on cultural, historical and ethnographic aspects contribute to the preservation of local traditions and increase the attractiveness of the territories for tourists. The positive impact of excursions on the region’s economy is also considered: excursion activities stimulate demand for local products, crafts and services, which in turn contributes to the development of small businesses, the creation of new jobs and the strengthening of economic resilience of communities. The article highlights the main challenges facing the excursion business in the context of sustainable tourism. In particular, the article discusses the need to improve the professional level of guides in the field of sustainable development, adaptation of excursion programmes to the requirements of environmental standards and active involvement of local communities in tourism activities. The importance of cooperation between government, business and local organisations to ensure the sustainable development of tourist regions. Thus, the excursion business, focused on the principles of sustainable development, has a significant potential for preserving natural and cultural heritage, ensuring economic growth and improving the quality of life of the local population.